Analisis Efektivitas Birokrasi dalam Pelayanan Publik (Studi Kasus Pemerintah Kabupaten Biak Numfor) - Hamjah Bonso; Busyairi Ahmad (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
The existence of bureaucracy is a logical consequence of the main task of the state (government) to organize social welfare. The state is required to be involved in producing goods and services needed by its people (public goods and services), either directly or indirectly. This study aims to determine the effectiveness of the related bureaucracy in public services in the Biak Numfor district government. This study uses the "triangulation" method, which combines qualitative and quantitative methods with data collection techniques by means of interviews, documentation, and questionnaires. This research shows that the local government, in this case the Department of Population and Civil Registry, in the service of making electronic identity cards has been effective. This can be seen from Actors, Interdependency and Frame getting a score of 2.05 (high), Interaction and Complexity getting a score of 1.35 (moderate), Institutional Features getting a score of 1.55 (moderate), and Network Management getting a score of 2.3 (high). Whereas the Regional Revenue Agency in making NPWPD services and tax payments which are divided into two types of services namely offline and online have been very effective where Actors, Interdependency and Frame get a score of 2.1 (high), Interaction and Complexity get a score of 2.3 (high) Institutional Features scored 2.05 (high), and Network Management scored 2.5 (high).